Evaluation of optimum time for intravenous cannulation after sevoflurane induction of anesthesia in different pediatric age groups - Kanil Ranjith Kumar; Renu Sinha; Ravindran Chandiran; Ravinder Kumar Pandey; Vanlal Darlong; Chandralekha (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: The ideal time for intravenous (IV) cannulation following inhalational induction in children is debatable. The effect of age on this time has not been studied. We evaluated the optimum time for IV cannulation after sevoflurane induction of anesthesia in different pediatric age groups. Material and Methods: A prospective interventional study based on Dixon's sequential up and down method was conducted in children of age 1-10 years. They were grouped according to their age - Group 1: 1-3 years, Group 2: >3-7 years, and Group 3: >7-10 years. Anesthesia was induced with 8% sevoflurane in 5 L of 100% oxygen. IV cannulation was attempted at 3.5 min in the first child in each group. The time for cannulation in the next child was stepped up or down by 30 s depending on positive or negative response, respectively, in the previous child. Children were recruited till a minimum of six pairs of failure-success sequence which was obtained in each group. The mean of midpoints of the failure-success sequence was calculated to obtain the time for cannulation in 50% of the children in each group. Results: Total number of children in Groups 1, 2, and 3 were 24, 23, and 24, respectively. The mean (95% confidence level) time for IV cannulation after sevoflurane induction in Groups 1, 2, and 3 was 53.6 (40.0-67.1), 105 (62.6-147.4), and 143.6 (108.8-178.4) s, respectively. This time was significantly shorter in Group 1 compared to those in Groups 2 and 3. Conclusion: The optimum time for IV cannulation in 50% of the children after sevoflurane induction of anesthesia was shorter in children of age 1-3 years than in older children.